2017
DOI: 10.2147/clep.s129268
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia: a review of definitions used in clinical trials evaluating antihyperglycemic drugs for diabetes

Abstract: ObjectiveTo understand the severity and potential impact of heterogeneity in definitions of hypoglycemia used in diabetes research, we aimed to review the hypoglycemia definitions adopted in randomized controlled trials (RCTs).MethodsWe reviewed 109 RCTs included in the Canadian Agency for Drugs and Technologies in Health reports for the second- and third-line therapy for the patients with type 2 diabetes (T2D).ResultsNearly 60% (n=66) of the studies reviewed presented the definitions for overall hypoglycemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 22 publications
0
29
0
2
Order By: Relevance
“…There were a number of limitations to this study. As anticipated, the definitions of hypoglycaemia were heterogenous and included varying classifications of severity, symptomology, documentation, ascertainment, collection, reporting and handling of patients with hypoglycaemia . To overcome this, our primary outcome was any hypoglycaemia, irrespective of the definitions and classifications used by each study.…”
Section: Discussionmentioning
confidence: 99%
“…There were a number of limitations to this study. As anticipated, the definitions of hypoglycaemia were heterogenous and included varying classifications of severity, symptomology, documentation, ascertainment, collection, reporting and handling of patients with hypoglycaemia . To overcome this, our primary outcome was any hypoglycaemia, irrespective of the definitions and classifications used by each study.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones are agonists of the peroxisome‐proliferator active receptor (Balijepalli et al, ), which may reduce IR and promote the expression of growth factors such as BDNF (Kariharan et al, ). Clinical studies indicate that in patients with cognitive impairment or AD in early stages, thiazolidinediones improve long‐term memory functioning (Galimberti & Scarpini, ) .…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…However, important heterogeneity exists among these guidelines (Table ), which has contributed to differences in the way hypoglycaemia has been reported across clinical trials . A meta‐analysis of trials included in the Canadian Agency for Drugs and Technologies in Health Reports examined the way hypoglycaemia was reported in trials of glucose‐lowering drugs, including oral antihyperglycaemic drugs, fast‐acting insulins and BIs . This revealed that definitions of hypoglycaemia were included in only 60% of these trials, and few of these definitions followed American Diabetes Association (ADA) and European Medicines Agency (EMA) recommendations for definition of hypoglycaemia as blood glucose (BG) of ≤3.9 mmol/L (≤70 mg/dL), or <3.1 mmol/L (<56 mg/dL), which was recommended by the EMA prior to 2012 …”
Section: Diversity Of Hypoglycaemia Assessment and Reporting In Randomentioning
confidence: 99%
“…7 A meta-analysis of trials included in the Canadian Agency for Drugs and Technologies in Health Reports examined the way hypoglycaemia was reported in trials of glucose-lowering drugs, including oral antihyperglycaemic drugs, fast-acting insulins and BIs. 36 This revealed that definitions of hypoglycaemia were included in only 60% of these trials, 36 and few of these definitions followed American…”
Section: Hypoglycaemia Classification and Glycaemic Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation